Avaliação geotécnica do leito e de sistema de drenagem em estrada não pavimentada - Haraguchi, Marcelo Tsuyoshi (2017)
The unpaved roads have an importance for the social and economic development of Brazil, since it serves as the paved roads connection. The erosion caused by water in the bed and the banks of these roads is one of the main factors for its degradation. Knowing the resistance of the road to California Bearing Ratio (CBR) and trafficability is the beginning of the behavior check to not degrade. Associating alternatives to avoid erosion through accumulation basins also highlights aspects of conservation and environmental preservation. The pilot road is located in the municipality of Goiânia - GO, having as reference the road GO 462 exit to the municipality of Nova Veneza. This road is 600 m long, with an average slope of 5%, and has been topographically mapped every 20 m. The criterion of both unpaved roads and accumulation basins is the basis of this work. The soil considered is the typical Acridric Red Latosol. From the identification of the defects caused by the accumulation of water on the runway is important for decision making. In this case, as the road is docked, it has decided to plunge the cross section around 4% and associate the accumulation basin. For the dimensioning of these circular basins, the 6-m diameter and 2.0 m deep program was used for the ESTRADAS program. In the first treatment the accumulation basin is connected to the road by an open channel of 10 m in length. In the second, in the canal is planted Batatais grass with length of 10 m. In the third one is used a pre-basin of 3 m in diameter and 1,5 m of depth connected to the road by an open channel with 5 m of length. The bedroom also has a pre-basin with the same characteristics but with vegetated canal with Batatais grass of 5 m. The width of the channels is fixed at 0.80m and are set at 20m by 20m. The road subdivided in study is 5 m wide and 20 m long, totaling 100 m2 of area of influence for the collection of drainage of rainwater and sediments generated in this road. Maintaining the infiltration dynamics is another objective of this work. For this, physical attributes tests were performed before and after the construction of the basins and changes in the section of the road. The arrival of the sediments in the basins and pre basins significantly alter the physical attributes of direct interference in the infiltration dynamics or in the hydraulic conductivity. We simulated the variability of hydraulic conductivity in the laboratory with the permanent addition of sediments collected from the road, since there was no significant statistical difference in the field and in the laboratory. The estimation of sediments that reach the pre-basin was done using the SURFER program. As the hydraulic conductivity was not completely annulled, the microtomography was used to verify porosity behavior with depth. It was verified that sealing or inability to infiltrate occurs in successive layers and not only superficially as hypothesis. The variability of the porosity corroborates this finding. The CBR presented an average of 38%, enough for the road to be used as sub base, with great resistance. The best treatment is the pre-basin with vegetated canal, followed by vegetated canal, followed by pre- basin without vegetated canal, followed by non-vegetated canal. The cost of implementation, since the project, change of section and opening of the basins and channel was R $ 24240.0. Since there are 24 treatments, then it is R $ 1010,00/treatment.